Secondary hormonal alterations in short-term severe hypothyroidism; in the focus: Apelin and copeptin - Gergics, Marin; Pham-Dobor, Gréta; Horváth-Szalai, Zoltán; Kőszegi, Tamás; Mezősi, Emese; Bajnok, László (Frontiers in Endocrinology, 2022)
Objective: This study aimed to investigate the complex interactions of thyroid hormone, apelin, and copeptin in the fluid-ion homeostasis of patients with severe transitory hypothyroidism. Methods: In this prospective observational study, thirty-nine patients (ECOG: 0; 11 men, 28 women, mean age: 50.3 ± 14.9 years) were investigated during short-term severe hypothyroidism due to surgical removal of the thyroid gland and after adequate thyroid replacement therapy. Besides the routinely available lab tests, copeptin and apelin levels were determined using ELISA. Results: In the hypothyroid state, apelin concentration was lower, while copeptin levels did not differ compared to the euthyroid condition. Apelin showed a positive correlation with copeptin (p = 0.003), sodium (p = 0.002), NT-proBNP (p <0.001) and fT4 (p <0.001) and a negative correlation with TSH (p <0.001). In multivariate linear regression models, copeptin and TSH proved to be significant independent predictors of apelin levels, of which TSH had an explanatory power of 48.7%. Besides apelin, copeptin only correlated with sodium (p = 0.046). Sodium levels were negatively associated with TSH (p = 0.004) and positively with ACTH (p = 0.002) and cortisol (p = 0.047), in addition to copeptin. None of the parameters were independent predictors of serum sodium levels in a multivariate regression model. Conclusions: In short-term severe hypothyroidism, serum apelin level is markedly decreased, which may predispose susceptible patients to hyponatremia, while the level of copeptin is unchanged. TSH and copeptin are independent predictors of apelin concentration, of which TSH is stronger.